'The super-fats, the middlies and the barely-fats' : Naming and describing the body in plus-size fashion blogs - Limatius, Hanna (The Royal Gustavus Adolphus Academy for Swedish Folk Culture / Kungliga Gustav Adolf Akademien, 2023)
This article investigates the practices of naming and describing bodies in plus-size women’s fashion blogs. Building on Jeffries’ (2007) work on the construction of bodies and bodily processes in women’s magazines, I explore how bloggers use language to construct their identities through references to bodily characteristics. I investigate terms the bloggers use to describe the plus-size body, as well as the connotative features of these terms. In addition, I analyse the use of three terms that were used to describe bodies that are not plus-size: thin, slim, and skinny. The results demonstrate that, while the bloggers build counter-discourse to the mainstream media discourses that construct fatness as a negative characteristic, they also maintain particular hegemonic discourses on beauty, sexuality and gender.
Keywords: body positivity; fashion blogs; fat acceptance; identity; othering; weight stigma; identity (mental objects); gender; fi=Viestintätieteet|en=Communication Studies|